Zooplankton composition in five oxbow lakes from the Upper Juruá River, Acre State, Brazil - dos Santos, Maria José Alencar (2013)
This work was conducted in five oxbow lakes located between Cruzeiro do Sul and Rodrigues Alves counties (Acre State, Brazil), to provide additional information about the composition of zooplankton assemblages in the Upper Juruá River. Samples were collected from May 2009 to May 2010, and fixed with 4% formalina. The numeric density (ind.m -3 ) was obtained from subsequent sub-samples (1 mL). The study recorded 19 zooplankton families. Rotifers showed higher species richness (81 species), followed by cladocerans (3 species) and various forms of copepods and other organisms. Higher zooplankton means of numeric density was found in Novo Lake, with rotifers (1879 ind.m -3), cladocerans (207 ind.m -3), copepods (870 ind.m -3 ). Diversity and numeric density were similar to other Neotropical aquatic ecosystems.